Analysis of the level of groundwater environmental damage due to community activities in the Parangtritis coastal area, DIY Province - Puspita, Ayunda MIlla; Santosa, Langgeng Wahyu; Adji, Tjahyo Nugroho (Journal of Degraded and Mining Lands Management, 2023)
This study aimed to analyze the level of damage to the groundwater environment in terms of groundwater quality in the coastal area of Parangtritis and its surroundings. This research study unit is based on the landform unit and activities of the community. The research location is located in Parangtritis Village, Yogyakarta Special Region (DIY) Province. This study used a descriptive quantitative analysis as its method of analysis. This study used primary data obtained by testing groundwater samples in the laboratory. The groundwater sampling technique is carried out using the purposive sampling area. Groundwater sampling was carried out on eleven land units. The determination of the level of environmental damage to groundwater is carried out using the Pollution Index (IP) method referring to the Regulation of the Minister of Environment Number 115 of 2003. The results showed that the environmental damage to groundwater shows the quality status of lightly polluted water with pollutant index values ranging from 1.244-4.176 with variable pollutants chemical oxygen demand (COD), dissolved oxygen (DO), ammonia, nitrate, phosphate, and total coliform as well as with sources of pollutants from settlements, livestock, and agricultural activities.